2019
DOI: 10.3390/su11102854
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fertilizers on Biomass and Biodiversity on a Semi-Arid Grassland of Northern China

Abstract: Semi-arid grassland in northern China faces degradation and desertification problems, with fertilizer application appearing to be a potential solution by improving soil fertility and plant fields or biodiversity. In this study, mineral and organic fertilizers were used in a semi-arid natural grassland in Hebei Province for three years. The plant characteristics, biomass and species diversity index were assessed and analyzed. In the years 2016 and 2017, mineral fertilizers (RC) significantly increased the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…The diversity index (Shannon) was higher in the fertilized plots (2.575-chemical fertilizer, 2.642-diluted fertilizer type I, 2.752-diluted fertilizer type II, and 2.637-organic fertilizer) than in the control plot (1.825). This result is in accordance with other studies that report the increase in species richness by the utilization of organic fertilizer (Tong et al, 2019) or different type of fertilizers (mineral nitrogen or manure) (Samuil et al, 2013). However mineral fertilizers are responsible for long-term nitrogen deposition and can decrease biodiversity (Stevens et al 2004;Pallett et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The diversity index (Shannon) was higher in the fertilized plots (2.575-chemical fertilizer, 2.642-diluted fertilizer type I, 2.752-diluted fertilizer type II, and 2.637-organic fertilizer) than in the control plot (1.825). This result is in accordance with other studies that report the increase in species richness by the utilization of organic fertilizer (Tong et al, 2019) or different type of fertilizers (mineral nitrogen or manure) (Samuil et al, 2013). However mineral fertilizers are responsible for long-term nitrogen deposition and can decrease biodiversity (Stevens et al 2004;Pallett et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…The use of organic fertilizers (Karmaoui, 2019) is an example. These organic fertilizers include animal manure, compost, and crop residues are important elements that promote soil quality (Frossard et al, 2009) and then support biodiversity (Tong et al, 2019). For desert sand dunes, there are three categories of fixation systems, mechanical, biological, and mechanical-biological, and the respondents ranked seasonal migration as an option that has a moderate impact on desertification.…”
Section: Discussionmentioning
confidence: 99%
“…Natural grasslands rich in species composition [24] and fertilizing improves the growth and development of dominated species that higher species composition across all the treatments including the urea applied plots. It was also reported that use of fertilizers increasing plant biomass production and biodiversity in semi-arid grasslands [14]. The average legume proportion was higher in the unfertilized plots than in the fertilized plots and this may indicate nitrogen fertilizer had an indirect suppressing effect on the proportion of legumes by inducing luxuriant growth and hence dominance of the grasses.…”
Section: Species Compositionmentioning
confidence: 90%
“…Nitrogen fertilizer application improves above ground biomass of any plant crops [13]. Phosphorus improves the growth of legumes and plant species composition generally and a Poaceae pasture in specific [14]. Nitrogen and phosuphorus fertilizers combined application could improve the aboveground plant biomass [15] and have positive effects on composition diversity of plant species [16].…”
Section: Introductionmentioning
confidence: 99%